Ethnicity and class in urban residential mobility: some empirical observations. - Lee , Boon Thong (Universiti Kebangsaan Malaysia, 1980)
Residential mobility affects the internal structures of cities by intensifying or adulterating specific characteristics of existing residential areas. In this respect, the volume of movements and more important, the directional biasnesses are important determinants of city structures. A case study of six different residential areas in Kuala Lumpur confirms the model of mobility destination biasnesses according to ethnic and/or socio-economic status. This implies a perpetuation of existing socio-economic and ethnic residential structures and any attempts to contain this trend would require more attention and research into realms such as attitudes and behaviourism.